Sistema Web para la gestión de novedades académicas estudiantiles en la inspección general de la Unidad Educativa Corina Parral de Velasco Ibarra del cantón Chimbo, año 2023. - Banshuy Morocho, Jonathan Fabricio (2023)
This technological project of curricular integration deals with the development of a Web System for the Management of Student Academic News in the General Inspectorate of the Corina Parral de Velasco Ibarra Educational Unit of the Chimbo canton, which automates the registration processes and sending of the academic parts that the students have as an observation in the classroom lectionary with the different teachers of each subject. The implementation of this technological, feasible and innovative solution was carried out applying the XP (Extreme Programming) methodology since it is the most used for agile software development projects; the same one that started with the planning where the requirements of each one of the processes that are carried out within the general inspection were investigated, as well as the collection of information about the users and their interaction; In the designs, the creation of the reaction entity model, creation of the database and the design of interfaces were carried out; in the coding stage, the PHP, MYSQL, Dreamweaver tools were used as 4GL tools to generate the first prototype; and in the testing stage, functional, non-functional, unitary, interface, integration, usability, scalability, reliability and performance tests were carried out, which served to give precision, safety and efficiency to all automated processes; All the data and information has been collected in the real context and registered within the computer system, verifying the rigorous functionality and the guarantee of the quality of the software. Finally, both the conclusions and the recommendations reached after the implementation of the Web System within the Educational Unit subject to study are drawn up. Keywords: Information System, web platforms, XP methodology, automation of academic news, technological tools.